Optimalisasi Peran Tim Pendamping Keluarga (TPK) Dalam Penurunan Stunting Di Dinas P3APPKB Kabupaten Blitar - Hafidoh, Siti Nur; Askafi, Eka; Mutiara, Nisa (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
The Blitar Regency Government prioritizes available resources to increase the coverage of services to the target group for the Acceleration of Stunting Reduction which includes adolescents, prospective brides/potential couples of childbearing age, pregnant women, lactating mothers and children aged 0 (zero) to 59 (fifty nine) months in order to support national priorities This st udy aims to analyze how to optimize the role of the family assistance team in reducing stunting at the P3APPKB Office of Blitar Regency. The research method used is descriptive research with a qualitative approach. Informants of this study amounted to 8 people. Data analysis in this study used triangulation and was strengthened by focus group discussions. Based on the research results, it was found that the role of the family assistance team is very important in the context of reducing stunting in Blitar Regency, because in addition to implementing team assistance, it also makes innovations so that the assistance role can run optimally. However, there are still a number of obstacles that must be corrected, such as the lack of quality human resources for the family assistance team and the lack of massive outreach to the community.